Neon in carbon nanopores: wetting, growth mechanisms and cluster structures: Classical Cryocrystals - Krainyukova, N.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Low-temperature high-energy (50 keV) electron diffraction study of size-dependent structures and growth mechanisms of neon samples in multiporous «amorphous» carbon films is presented. Electron diffractograms were analyzed on the basis of the assumption that there exists the cluster size distribution in deposits formed in substrate and multi-shell structures such as icosahedra, decahedra, fcc and hcp were probed for different sizes up to approximately 3·104 atoms. The analysis was based on the comparison of precise experimental and calculated diffracted intensities with the help of the R (reliability) — factorminimization procedure. Highly reproducible discrete distribution functions of sizes and structures werefound. The time-dependent evolution of diffractograms at earlier stages of growth was revealed. Initially distinct diffraction peaks gradually «disappeared» although the total electron beam absorption evidenced that deposited neon was preserved in the porous substrate. We ascribed this effect to diffusion-like gas penetration from larger to smaller pores which resulted in a highly dispersed or even disordered substance. Evidently,clusters initially grown during deposition were later soaked by a sponge-like substrate due to capillary forces.